Innovative M&E from the Sandbox and beyond - Vester, Søren; Tran, Samuel (2023)
In this blog we are sharing a digest of some of the many useful and in novative monitoring, evaluation and learning resources and efforts tha t have come through the M&E Sandbox in 2022. A lot of these resources have been shared by our community in response to the overwhelmingly po sitive feedback from the launch of the Sandbox (please keep them comin g!). We hope you find it useful. We have grouped these efforts and res ources under six broad questions: - How do we measure systems transfor mation? - How do we know if we are on track? - How do we rethink compl exity and independence in evaluation? - Why, how and for whom do we me asure? - How do we generate insights and learn? - How do we make decis ions and adapt?